` Study the Effect of Nano-Indian Costus Extract on Thyroid Gland Injury - Majeed, Neean F.; Ali, Alyaa H.; Mazhir, Sabah N.; Abdullah, Hadder M. (Iraqi Journal of Science, 2024)
The thyroid is an endocrine gland that produces and secretes triiodothyronine (T3), and thyroxine (T4) hormones. These hormones are essential for maintaining body homeostasis. Indian costus is a medicinal plant used in the treatment of thyroid disorders. The aim of the study is to use Indian costus in its particles and nanoparticles to treat the thyroid, which was infected with an overdose of melatonin. Nano Indian costus was prepared using microwave plasma and pulsed laser deposition (PLD). To determine the most effective technique for creating the Indian costus nanoparticles, the material was examined using an atomic force microscope (AFM) in its bulk and nanoparticle forms. It was found that the microwave plasma method gave better results than PLD, where the average nanoparticle diameter was 21.11nm for the microwave plasma method and 40.02nm for the PLD. Thyroid hormones regained their normal levels of T3 and T4 after receiving Indian costus nanoparticles prepared by microwave plasma, which proved more effective than Indian costus nanoparticles prepared by PLD.